Manuscrito cuervo, humor in the absurd tragedy of war - Berchez, Amanda [UNESP]; Oliveira, Katia Aparecida da Silva (Univ Sao Paulo, Fac Filosofia, 2024)
This study has as its hypothesis humor was the mechanism Max Aub managed in Manuscrito cuervo to narrate the traumas acquired on several occasions, addressing the burden carried from the experienced tragedies. Among them, the Spanish Civil War, during which he was labeled a dangerous communist and consequently sent to the concentration camp of Le Vernet. This helps us understand the author's in-between condition (born in Paris, affiliated with Spain, returned to France as a prisoner of war and ultimately took refuge in Mexico), that seemed to represent an impossibility of belonging and situating his individuality. It was from this standpoint that he summoned a raven to record experiences, particularly of war, while also delving into related issues like exile and identity. Through humor, Aub breached the power and impenetrability of the horrors experienced at the hands of other humans, although he never entirely detached from them. Once a witness, always a witness.
Keywords: Max Aub; Manuscrito Cuervo; Comic; Spanish Civil War; Francoism